2011
DOI: 10.1159/000330105
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Degree of Flowering Implicates Multiple <i>Chenopodiaceae/Amaranthaceae</i> Species in Allergy

Abstract: Background: IgE-mediated sensitization to the Chenopodiaceae/Amaranthaceae families is a cause of allergic symptoms in arid areas. Salsola kali and Chenopodium album are considered the main species responsible; however, there is a discrepancy between the pollination period of these two plants and clinical symptoms. The objectives of this study were to identify new Chenopodiaceae/Amaranthaceae members with sensitization capacity and to correlate symptoms, pollen counts and degree of flowering of different speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(19 reference statements)
0
5
0
2
Order By: Relevance
“…pollen concentration. 6,15 Although six species of Amaranthus can be found in Thailand, this study identified only three species: A. spinosus, A. hybridus, and A. viridis, commonly found in the Bangkok Metropolitan Region. These three species had different characteristics.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…pollen concentration. 6,15 Although six species of Amaranthus can be found in Thailand, this study identified only three species: A. spinosus, A. hybridus, and A. viridis, commonly found in the Bangkok Metropolitan Region. These three species had different characteristics.…”
Section: Discussionmentioning
confidence: 75%
“…Pollen allergen surveys showed that pollen of Amaranthus can be found in the atmosphere throughout the year. 6,15 A study performed in Spain showed that the maximum concentration of Amaranthus pollen was found between June and October each year 6,15,16 , while another study performed in Romania showed the highest daily pollen concentration between late July and mid-August 7 . Previous airborne pollen survey in Bangkok showed that the peak of Amaranthus pollen count occurred between November and January with the highest concentration in December.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After immunological characterization, we determined that the various isoforms of Sal k 4 show various IgE‐binding capabilities, and suggests a hypoallergenic nature for rSal k 4.02 in comparison to rSal k 4.03 and rChe a 2 because it binds significantly lower levels of IgE. Although the possibility cannot be discarded that this response is due to a lower IgE cross‐reactivity of Sal k 4.02 to other primary sensitizing profilins in other pollens of the environment, it should be taken into account that S. kali pollen is a main source of sensitization for the Zaragoza patient population , and thus S. kali profilin is a primary sensitization source. In the province of Jaén, S. kali co‐exists with olive tree cultivars, the main agriculture crop, and is an important source of allergenic pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of flowering may help to identify specific grasses responsible for pollen allergy by identifying the pollination season of different species [8]. C dactylon has been found to flower later than temperate grasses [6], possibly explaining the onset of symptoms in grass-sensitized patients in late June or July.…”
Section: Introductionmentioning
confidence: 99%